The role of human competency development in achieving competitive advantage: A case study of the SAIDAL complex - Gharbi, Zahia; Hadjadj, Abderraouf (The International tax journal, 2025)
The study aims to shed light on the concept of human competency development in pharmaceutical manufacturing institutions, and to assess the extent of its application within the SAIDAL (Algerian Company of Pharmaceutical Industries). It also seeks to measure its impact on achieving competitive advantage at SAIDAL. To reach the study’s objective, we adopted a descriptive-analytical approach and relied on a questionnaire as an auxiliary tool. The study population consisted of a group of employees from SAIDAL (Dar El Beïda Unit), with a sample of 54 workers. A total of 83 questionnaires were distributed, 56 were returned, and 2 were excluded for being invalid. The results were statistically analyzed using the SPSS software for social sciences. We arrived at several conclusions, including the presence of a good and acceptable understanding of the concept of human competency development among SAIDAL employees, attributed to the company’s attention to human competencies and the commitment of its employees to good behavior, in addition to the presence of individuals with high skills and knowledge. There was also a clear understanding of the concept of competitive advantage.